Delegation of Authority in Terms of European Integration - Vdovenko, Tetyana (Journal of Danubian Studies and Research, 2023)
Much attention is currently being paid to the process of delegation of authority. The purpose of the article is to study theoretical and practical issues of delegation of authority in modern European society. Delegation means the transfer of tasks and powers to a person who assumes responsibility for their implementation. The growth and development of companies currently leads to a significant increase in the amount of work performed by the head. The manager is physically unable to perform such a volume of work, there is a need to transfer part of the work and functions to subordinates, at the same time, additional powers are transferred to them. The manager is relieved of performing a significant part of the work and he has time to solve the main problems of the organization, which is the most important positive side of delegation of authority.